The Prosperity Gospel and an Unprosperous Reality in Post-Apartheid South Africa: Conservative Evangelical Responses to Charismatic Christianity - Bafford, Douglas (Unpublished, 2019)
The global rise of Pentecostalism and other relatively charismatic forms of Christianity has prompted extensive commentary in the social sciences, whether through the lens of syncretic cultural practice, psychological experiences of transcendence, or the socioeconomic logics of millennial capitalism. Despite a growing popularity on the South African religious landscape, charismatic leaders are not immune from suspicion within the popular media—from anxieties that their material gains are unjustified to claims their conduct is “cultish” or even “criminal.” Unsurprisingly, these criticisms are echoed among conservative evangelical Protestants whose more conventional Christian practice positions them against preachers who claim “spiritual gifts” for healing, worldly prosperity, and prophecy. Christians perturbed by the rise of charismatic followings describe them as trafficking in what they call the “prosperity gospel,” a false promise of material gain based on a misreading of biblical prophecy. While their condemnation of these Christian practices is trenchant, they share an ironic overlap with charismatics on other theological and social matters; consequently, tensions arise in how properly to attend to believers who are at once uncannily similar yet nevertheless socially excluded. Drawing on continuing ethnographic fieldwork with multiracial conservative evangelical congregations centered in Johannesburg, I trace discourses around the prosperity gospel that emerge from an intertwining of theological, social, and racial arguments. Although at some points evangelicals raise concerns via textual exegesis, they also contend that prosperity preaching is a socially unjust phenomenon that exacerbates existing racial gaps in wealth. I suggest that conservative responses to the rise of charismatic Christianity offer unique insights into ongoing debates about race, neocolonialism, and material inequalities in South Africa, as they mediate an uneasy relation between religious promise and the disappoiments of post-apartheid life. This work also contributes a more dynamic perspective of global Pentecostalism by examining its interactions with its discursive opponents.
free